Analisis Perbaikan Pengendalian Kualitas Produk Pintudengan Menggunakan Metode Six Sigma dan FMEAPada PD. Indah Mulya - Assyifa Sya’bani; Dene Herwanto (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
PD Indah Mulya is a trading company engaged in the wood processing industry, one of which is a door type product. In door production at PD Indah Mulya, there are usually defects such as splitting, sunken and porous. The defect needs to be corrected. The purpose of this study is to determine the percentage and factors that cause defects that most often occur and provide suggestions for quality improvement actions. The methods used are Six Sigma and Failure Mode Effect Analysis (FMEA) at the improve stage. Based on the results of the study, the percentage of product defects is 27% split, 42% concave defects and 30% porous defects. The type of defect that occurs a lot in PD Indah Mulya is a sunken defect. Sunken defects are usually caused by the type of wood used is young. Based on the results of RPN calculations for FMEA door production, several risks are obtained that have the highest priority level for making repairs to minimize the possibility of errors. Calculation The highest RPN value is 180 from the type of concave defect with the cause of inappropriate selection of raw materials. The recommendation for proposed improvements to overcome this problem is to conduct coaching for the raw material selection process